Using Excel to teach accounting as an integrated system - Stoycho Rusinov; Nadya Sokolova (Икономика и компютърни науки, 2025)
This paper introduces a novel approach to teaching accounting as an integrated system by utilizing Excel as an emulation-like environment for the real flow of accounting information in the bookkeeping process. Leveraging Excel’s widespread accessibility and computational capabilities, the proposed system allows students to engage with complex accounting scenarios that require understanding the flow and interaction of multiple accounting objects. The system supports accurate calculations, automated financial reporting, and flexibility in account management, enhancing adaptability to diverse educational settings. A key advantage is its ability to initiate the accounting process with a trial balance containing non-null entries, a feature often unavailable in subscription-based accounting software. This Excel-based system provides a practical and intuitive platform for conducting examinations and fostering a deeper understanding of accounting principles, bridging the gap between theory and practice in accounting education.